2021
DOI: 10.1128/mbio.02148-21
|View full text |Cite
|
Sign up to set email alerts
|

Novel Gut Microbiota Patterns Involved in the Attenuation of Dextran Sodium Sulfate-Induced Mouse Colitis Mediated by Glycerol Monolaurate via Inducing Anti-inflammatory Responses

Abstract: The gut microbiota, which can be highly and dynamically affected by dietary components, is closely related to IBD pathogenesis. Here, we demonstrated that food-grade glycerol monolaurate (GML)-mediated enhancement of Bifidobacterium and fecal SCFAs could be responsible for the anticolitis effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…Lachnospira , Coprococcus and Ruminococcus ) and even higher proportions of Actinomyces and Turicibacter . Although not much information is available on these microorganisms, Turicibacter has recently been identified as a potential gut inflammation-related taxon, 32 as well as a possible marker of the chronic-progressive form of MS, 33 and it is known that Actinomyces could aggravate lesions caused by inflammatory states by inducing changes in the enteric environment and modulating immune responses. 34 As expected, MS-related GM alteration was more severe in patients with progressive form, who were particularly enriched in Streptococcus and [ Ruminococcus ].…”
Section: Discussionmentioning
confidence: 99%
“…Lachnospira , Coprococcus and Ruminococcus ) and even higher proportions of Actinomyces and Turicibacter . Although not much information is available on these microorganisms, Turicibacter has recently been identified as a potential gut inflammation-related taxon, 32 as well as a possible marker of the chronic-progressive form of MS, 33 and it is known that Actinomyces could aggravate lesions caused by inflammatory states by inducing changes in the enteric environment and modulating immune responses. 34 As expected, MS-related GM alteration was more severe in patients with progressive form, who were particularly enriched in Streptococcus and [ Ruminococcus ].…”
Section: Discussionmentioning
confidence: 99%
“…48 Notably, Mo et al found that GML could attenuate mouse colitis through the enhancement of Bifidobacterium and fecal short-chain fatty acids (SCFAs). 9 Furthermore, it has also been reported that Bifidobacterium could strengthen the intestinal epithelial tight junction barrier and prevent intestinal inflammation. 49,50 Given that 1600 mg kg −1 GMD supplementation could also increase the Bifidobacterium abundance, we hypothesized that 1600 mg kg −1 GMD would improve the intestinal barrier function by increasing the Bifidobacterium abundance, which would then lead to a decrease in the serum levels of pro-inflammation cytokines.…”
Section: Food and Function Papermentioning
confidence: 99%
“…6,7 The remarkable effects of GML in attenuating metabolic syndrome and inflammation have been verified. 8,9 However, although many studies have been conducted so far on the antibacterial effect of GMD in vitro, 1,10 the overall evaluation of the effects on the whole metabolism and host health is still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The protective effect of GML on colitis and the potential dysbiosis-related mechanism were also assessed [ 48 , 51 ]. GML pretreatment is superior to GML cotreatment for colitis.…”
Section: Emulsifiersmentioning
confidence: 99%